2015
DOI: 10.1037/ccp0000032
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral economic predictors of brief alcohol intervention outcomes.

Abstract: Objective The present study attempted to determine if behavioral economic indices of elevated alcohol reward value, measured before and immediately after a brief alcohol intervention, predict treatment response. Method Participants were 133 heavy drinking college students (49.6% female, 51.4% male; 64.3% Caucasian, 29.5% African American) who were randomized to one of three conditions: motivational interviewing plus personalized feedback (BMI), computerized personalized feedback intervention (e-CHUG), and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
117
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 112 publications
(134 citation statements)
references
References 58 publications
(108 reference statements)
12
117
2
2
Order By: Relevance
“…Although we did not examine these relationships in the context of a quit attempt, considering that current depressive symptoms are associated with poor cessation outcomes 49,50 and that elevated alcohol demand is associated with poor alcohol intervention response, 51 our results suggest that one factor that could complicate a smoking cessation attempt for an individual with current elevated depressive symptoms is the heightened value of a cigarette to a smoker when experiencing increases in NA. For example, recent smoking cessation trials utilizing ecological momentary assessment throughout the course of a quit attempt have found that change in NA both prior to 52 and following initiation 53 of a quit attempt is predictive of success in quitting smoking.…”
Section: Discussionmentioning
confidence: 90%
“…Although we did not examine these relationships in the context of a quit attempt, considering that current depressive symptoms are associated with poor cessation outcomes 49,50 and that elevated alcohol demand is associated with poor alcohol intervention response, 51 our results suggest that one factor that could complicate a smoking cessation attempt for an individual with current elevated depressive symptoms is the heightened value of a cigarette to a smoker when experiencing increases in NA. For example, recent smoking cessation trials utilizing ecological momentary assessment throughout the course of a quit attempt have found that change in NA both prior to 52 and following initiation 53 of a quit attempt is predictive of success in quitting smoking.…”
Section: Discussionmentioning
confidence: 90%
“…For example, interventions that enhance future time orientation (Sheffer et al, 2016) and present-focused attention/mindfulness (Ashe et al, 2015) or provide contingent reinforcement (Weidberg et al, 2015b) appear to reduce DD. Additionally, brief motivational (Dennhardt et al, 2015) or personalized feedback interventions (Murphy et al, 2015) reduce the rewarding value of substances. Smokers with psychopathology may benefit from pre-cessation intervention that specifically targets (reduce) tobacco demand and DD, whereby increasing ability to manage withdrawal-induced urge and craving to tobacco that onset following a quit attempt.…”
Section: Discussionmentioning
confidence: 99%
“…Substance demand indices derived from purchase tasks for general preferences are related to frequency of substance use and dependence symptoms (MacKillop et al 2010a; Aston et al 2015; MacKillop et al 2016) and are predictive of therapeutic treatment response (MacKillop and Murphy 2007; Murphy et al 2015; MacKillop et al 2016). State-orientated purchase tasks have been found to complement other state measures of acute motivation (MacKillop et al 2010b; Acker and MacKillop 2013; Metrik et al 2016).…”
Section: Introductionmentioning
confidence: 99%